Executive functioning and verbal fluency in children with language difficulties. (October 2015) - Henry, Lucy A.; Messer, David J.; Nash, Gilly
Abstract: This study provided a detailed analysis of verbal fluency in children with language difficulties, and examined the relative contributions of executive functioning (executive-loaded working memory, switching, inhibition) and language ability to verbal fluency performance. Semantic and phonemic fluency, language, and executive functioning tasks were completed by 41 children with specific language impairment (SLI) and 88 children with typical development. Children with SLI showed difficulties with most aspects of verbal fluency (rates of output, errors, switching) relative to typical children. Language ability predicted nearly every aspect of phonemic fluency performance and some aspects of semantic fluency performance. The relationships between verbal fluency and executive functioning were modest: inhibition was related to error scores on the phonemic fluency task, but relationships with executive-loaded working memory and switching were absent. Educationally, these results emphasise the underlying importance of language abilities in generation tasks like verbal fluency, but point to the importance of inhibition skills for error monitoring. Interventions to improve search and generation abilities have the potential to offer broader benefits in the classroom for children with language difficulties. Highlights: Children with SLI had difficulties with most aspects of verbal fluency (phonemic and semantic) performance. Language ability predicted many aspects of verbal fluency performance. The executive skill of inhibition was related to the production of errors in the phonemic fluency task. Executive-loaded working memory and switching were not significantly related to verbal fluency performance.